Essential macro-minerals, crude protein and total antioxidant activity of powdered ginger and turmeric act varied drying methods - Barbosa, Gina B.; Alinapon, Criselda V.; Pabiona, Myrna G. (2022)
Drying is widely usedd and one of the most effective methods for food preservation. This study reports the macro-mineral, crude protein, and antioxidant activity of locally produced powdered ginger and turmeric using the air-, oven- and sun drying methods. Kjeldahl method, atomic absorption spectroscopy, and phosphomolybdenum method were used to determine the crude protein, macrominerals (K, Ca, and Mg), and total antioxidant activity (TAA), respectively. Highest TAA was observed in sun-dried turmeric (7.82 ± 4.97mg AAE/g dried sample) while the lowest TAA was observed in sun-dried ginger powder (2.14 ± 0.31 mg AAE/mg dried sample). The measured crude protein of turmeric ranged from 8.34 ± 0.93 - 8.54 ± 0.14% while 6.25 ± 0.42 - 7.41 ± 1.05% for ginger. Essential macro-minerals in turmeric and ginger at varied drying methods ranged from 0.07 to 2.21 % for K, 0.04 to 0.12 % for% for Mg, and 0.79 to 1.15 % for Ca. ANOVA revealed that the effects of drying methods were only significantly affected to Mg for turmeric and K and TAA for ginger. Crude protein and Ca content were not significantly affected by the drying methods in both turmeric and ginger powder. Others were not significantly different. Results of this study provide significant insights that prepared turmeric and ginger powder are good sources of crude protein, macro-minerals (Ca, Mg, K), and possess antioxidant properties. All drying methods studied are efficient in retaining the crude protein and calcium content of the ginger and turmeric powder, and the TAA of the turmeric powder.
Keywords: Minerals; Antioxidants; Ginger